The Long-Term Consequences of Childhood Maltreatment for Adult Survivors: A chronic price to pay - Guajardo, Antonia; Tadros, Eman (Utan Kayu Publishing, 2023)
Child abuse reports are made every ten seconds in the United States, a country with one of the poorest records among industrialized nations, reports an average of five children dying daily due to abuse and neglect in 2019. This literature review furnishes a synopsis and essential analysis of child maltreatment, including abuse and neglect, and examines its numerous processes and complex effects on individuals, families, and society. Childhood maltreatment can include physical, sexual, and emotional can lead to Adverse Childhood Effects (ACE). These effects may have a detrimental impact on one's development, social skills, immediate and long-term physical well-being, mental health, and mortality. Although parents and caregivers determine their children's rearing practice, there must be procedures in place for medical professionals and schools to intervene when childhood maltreatment occurs. Moreover, the definition of abuse and state laws vary; therefore, there is a necessity for universal designations as to what entails maltreatment and abuse, and deterrents must be put in place federally to reduce childhood maltreatment.